Transformation of ritual and folklore traditions in acting art - Sabirova A., Boldykov Z., Zhaxylykova M., Khalykov K., (Opción, 2019)
The objective of the research is to define the meaning and application area of ritual and folklore elements in modern performances. In the study of this phenomenon, we applied methods of cultural, art criticism and theatre criticism analysis. As a result, traditional Kazakh culture was characterized by high continuity related to the moral education of the younger generation, the spiritual improvement of an individual. In conclusion, in modern Kazakh theatre, acting continues to be a dominant artistic device which is instrumental in realizing the director‟s vision for the production.